Voyage in Time - Chen, Lei (The Canadian Art Teacher / Enseigner les arts au Canada)

(untitled) (Canadian Society for Education through Art / Société canadienne d’éducation par l’art, 2025)
Art exists with the ability to actualize an idea or concept. My work is a constant search for the best way to interpret my beliefs about myself and my world. I do not limit myself to one medium, style, or concept. Although I make paintings with traditional Chinese materials, such as rice paper, vegetable dyes, and mineral pigments, through visual means, I want to speak worldwide—an artistic language that blurs the boundaries of diverse cultures, ethical beliefs, and geographical locations. This series of paintings’ name, Voyage in Time, originated from a documentary film by Andrei Tarkovsky in 1983, which draws an analogy with the art of cinema through the romantic, misty beauty of poetry. I argue that art and education unfold their truth; it is a voyage in time—both the educators and students involve themselves and evolve in lifelong dialogues with self and each other. This series was made in 2016 when I started to create art through gouache using new techniques. It inspired me to inquire about the intrinsic link between forms and contents in paintings that are meaningful in various teaching processes or curricula if we view it as a combination of forms and contents. The youths in the artwork, holding flowers in their hands, imply metaphors that resonate with adolescence, nihility, confusion, richness, and hope as they encounter the complexity of life. I hope to motivate people to expand their imaginative associations of individual and general experiences beyond specific things and rise to a philosophical meditation on life.